Peningkatan Kemampuan Pedagogik Guru dalam Pembelajaran Daring melalui Penerapan Kuis Interaktif Daring - Helda Jolanda Pentury; Itsar Bolo Rangka; Anastasia Dewi Anggraeni (Universitas Muhammadiyah Semarang, 2021)
Learning from Home (BDR) in network (online) and offline (offline) is indeed a challenge for teachers in its application. Inaccurate and non-varied learning methods are problems that teachers often face, especially in online learning. Teachers also have to learn to be more creative in choosing learning media so that their students don't feel bored. Online learning can run well, be effective and fun it requires motivation and also creativity in these learning activities. Creativity is important because creativity is one of the factors that influence success in learning. If teachers are motivated and creative, they will improve their pedagogic ability well to achieve learning goals. The activity, which is carried out in the form of a webinar and workshop online for elementary and middle school teachers, increases the role of teachers professionally in intellectual, pedagogical, and creativity which can help develop the learning process given. The results of this activity are increasing teachers’ pedagogic competences in the selection and use of creative, varieties, and interactive. So, applying online interactive quizzes become solutions in increasing teachers’ pedagogic competence in learning and assessment, project or performance.